种电解锌酸浸渣资源化无害化利用方法 (2018)
种电解锌酸浸渣资源化无害化利用方法，包括以下步骤：将新鲜的电解锌酸浸渣、硅酸盐粉料或铝酸盐粉料、改性剂按质量比锌酸浸渣60～92:硅酸盐粉料/铝酸盐粉料7～38:改性剂1～10的比例配料，经混合，成型，固化为抗水性建筑材料制品。本发明方法简单、实用，且无二次污染；可永久性消除锌酸浸渣的重金属污染及隐患，利于水、土环境保护；能有效利用锌酸浸渣生产抗水抗盐蚀胶凝材料及建材制品，既为基建工程提供优质的材料，又可大幅减少传统的胶凝材料及建材制品的生产过程对环境资源和能源的消耗及环境的污染。 The invention discloses a harmless resource utilization method of zinc electrolysis acid leaching residue. The harmless resource utilization method comprises following steps: by mass, 60 to 92 parts of fresh zinc electrolysis acid leaching residue, 7 to 38 parts of a silicate powder material or an aluminate powder material, and 1 to 10 parts of a modifier are subjected to mixing, moulding, and curing so as to obtain water-resistant building material products. The harmless resource utilization method is simple and practical; no secondary pollution is caused; heavy metal pollution and hidden danger caused by zinc electrolysis acid leaching residue are eliminated permanently; the harmless resource utilization method is beneficial for water and soil environmental protection